Performance investigation and simulation of a diesel engine operating on seven-process cycle based on energy and exergy criteria - Gonca, Guven; Genc, Ibrahim; Sahin, Bahri (INDERSCIENCE ENTERPRISES LTD, 2023)
This work investigates energetic and exergetic performances of seven-process cycle which is combination of Dual-Miller and Takemura cycles based on parametrical and grid curves. The impacts of design parameters on the maximum performance characteristics are examined. In the results, the energy (1. law) and exergy (2. law) efficiencies are maximised by a determined range, and then they are minimised by raising engine speed. Power is enhanced by enhancing engine speed at constant compression, Takemura cycle, equivalence, and cut-off ratios. Power and efficiencies increase with raising cycle pressure ratio at constant compression, Takemura cycle, equivalence and pressure ratios. Power and efficiencies decrease with increasing exhaust temperature ratio and cut-off ratio at constant compression ratio, Takemura cycle ratio, equivalence ratio and engine speed. They enhance with increasing pressure ratio and cycle temperature ratio at constant compression ratio, Takemura cycle ratio, engine speed and cut-off ratio.
Keywords: Takemura cycle; Dual-Miller cycle; performance optimisation; exergy; internal combustion engines; MILLER CYCLE; Thermodynamics; Energy & Fuels